Prophylactic Vancomycin Drops Reduce the Severity of Early Bacterial Keratitis in Keratoprosthesis - Konstantopoulos, Aris (2015)
Background: Artificial cornea transplantation, keratoprosthesis, improves vision for patients at high risk of failure with human cadaveric cornea. However, post-operative infection can cause visual loss and implant extrusion in 3.2–17% of eyes. Long-term vancomycin drops are recommended following keratoprosthesis to prevent bacterial keratitis. Evidence, though, in support of this practice is poor. We investigated whether prophylactic vancomycin drops prevented bacterial keratitis in an animal keratoprosthesis model.